2009
DOI: 10.1002/jnr.22035
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a mitochondrial pathway to excitotoxic neuronal necrosis

Abstract: It is traditionally thought that excitotoxic necrosis is a passive mechanism that does not require the activation of a cell death program. In this study, we examined the contribution of the cytochrome c-dependent mitochondrial death pathway to excitotoxic neuronal necrosis, induced by exposing cultured cortical neurons to 1 mM glutamate for 6 hrs and blocked by the NMDA antagonist, dizocilpine. Glutamate treatment induced early cytochrome c release, followed by activation of caspase-9 and caspase-3. Preincubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…No treatment could eliminate all neuronal injury in hilus, suggesting a mechanism of injury distinct from CA1 and CA3. This is not surprising, since previous studies showed that SE-associated hilar neuronal injury involves at least two distinct mechanisms (Lopez-Meraz et al, 2010; Seo et al, 2009). …”
Section: Discussionmentioning
confidence: 55%
“…No treatment could eliminate all neuronal injury in hilus, suggesting a mechanism of injury distinct from CA1 and CA3. This is not surprising, since previous studies showed that SE-associated hilar neuronal injury involves at least two distinct mechanisms (Lopez-Meraz et al, 2010; Seo et al, 2009). …”
Section: Discussionmentioning
confidence: 55%
“…Over-activity of NMDA receptors can increase neuron death during epileptic seizures, stroke, trauma or neurodegenerative disorders (Choi, 1994a, 1994b; During et al, 2000; McDonald et al, 1990a, 1990b), and NMDA receptor blockade can provide neuroprotection with SE, ischemia or excitotoxicity (Brandt et al, 2003; Clifford et al, 1990; Frasca et al, 2011; Fujikawa, 1995; Rice and DeLorenzo, 1998; Seo et al, 2009; Starr and Starr, 1994). In addition, extrasynaptic NMDA receptors that contain NR2B subunits have been implicated with neurotoxicity, degeneration, and cell death (Fong et al, 2002; Hardingham et al, 2002; Milnerwood et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The conventional view that necrotic cell death is a passive process has been called into question by accumulating evidence that necrotic cell death may involve caspase-dependent, programmed mechanisms. In primary neuronal cultures, neuronal necrosis induced by chemical hypoxia and/or glutamate excitotoxicity depends on an orderly cell death program leading to caspase-3 activation, which has been described as “active necrosis” (Niquet et al, 2003; 2005; 2006; Seo et al, 2009). The present study shows that a caspase cascade (caspase-8 preceding caspase-3 activation) may contribute to SE-induced neuronal necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings raise the possibility that SE induces neuronal necrosis in the developing brain through a caspase-dependent program, but light microscopy could not unequivocally show whether necrosis and caspase activation occurred in the same cells. We have previously reported the contribution of a mitochondrial mechanism involving caspase activation to neuronal necrosis following hypoxia-ischemia or glutamate-induced excitotoxicity (Niquet et al, 2003, 2006; Seo et al, 2009). The present study used postembedding EM immunohistochemistry to examine these mechanisms in seizure-induced neuronal injury.…”
Section: Introductionmentioning
confidence: 99%